Cutting-edge greenhouse practices for better stigma yield and corm quality of saffron (Crocus sativus L.) - Qaryouti, Muien; Al-Soqeer, Abdelrahman; Abdelaziz, Mohamed E.; Gruda, Nazim S.; AlSahly, Saif; Alrasheed, Wafa; Althobiti, Sahar; Babiker, Omar; Sharafeldin, Mahmoud; Voogt, Wim (Frontiers in Plant Science, 2025)
Saffron (Crocus sativus L.) is among the world’s most expensive spices, prized for its red stigmas used as a flavoring and a natural dye. Saudi Arabia is a significant importer of saffron, but the high cost of importing quality corms makes it economically unfeasible relative to the potential income from saffron production. Additionally, the high temperatures and harsh conditions of open fields pose significant challenges for saffron cultivation in the region. We investigated saffron cultivation under controlled greenhouse conditions with cooling to address these issues. Our study examined three plant densities—200, 100, and 67 corms m-²—and two planting depths—8 cm and 13 cm—to assess their effects on plant growth, flower yield, stigma production, and new corm development. We found that higher plant density (200 corms m-²) increased flower, and stigma yields per unit area but decreased flower number, stigma production, and plant weight per individual plant. Deeper planting (13 cm) reduced new corm production, particularly at the highest density. The largest corms and the highest percentage of big corms were observed at the lowest density (67 corms m-²), with planting depth having minimal impact on corm production. Given the high cost of quality corms, balancing flower production per corm with reproductive capacity is crucial. Therefore, based on our findings, we recommend a moderate planting density of 100 corms m-² and a shallow planting depth of 8 cm. These conditions provide a more balanced approach, optimizing both flower yield and corm production. Implementing these recommendations could enhance the efficiency and sustainability of saffron cultivation in greenhouses with cooling, making it a viable option for regions with challenging growing conditions.